Black music matters : jazz and the transformation of music studies - Sarath, Ed (Rowman & Littlefield, 2018)
Black Music Matters: Jazz and the Transformation of Music Studies is among the first books to examine music studies reform through the lens of African American music, as well as the emergent field of consciousness studies. It is inspired by conversations on race and a rich body of literature on the place of black music in American culture.